The Manchester short splint: A change to splinting practice in the rehabilitation of zone II flexor tendon repairs. (June 2014) - Peck, FH; Roe, AE; Ng, CY; Duff, C; McGrouther, DA; Lees, VC
Introduction: The results of patients with primary zone II flexor tendon repairs rehabilitated using a traditional forearm-based splint were audited and compared with those who were managed in the Manchester short splint. Method: The short splint was fabricated to permit maximal wrist flexion and up to 45° of wrist extension with a block to 30° of metacarpophalangeal joint extension. A rehabilitation regimen consisting of early combined passive flexion exercises and active motion was employed. In 2011, 62 patients (76 digits) with a mean age of 34 years (range 14–58) were rehabilitated using the forearm-based splint (group A). In 2012, 40 patients (45 digits) with a mean age of 31 years (range 15–71) were rehabilitated using the Manchester short splint (group B). Results: Group B had significantly less flexion contracture at their proximal interphalangeal joints than group A at 6 weeks (median 15° versus 28°; p = 0.003) and 12 weeks (median 6° versus 18°; p = 0.024) postoperatively. At the final review, group B had a significantly greater arc of flexion at their distal interphalangeal joints (median 59° versus 30°; p < 0.001) and a greater proportion of patients with excellent/good Strickland's grades. There were three (3.9%) ruptures in group A and two (4.4%) ruptures in group B (p > 0.999). Conclusion: The use of a shorter splint would appear to enhance the outcomes whilst preserving repair integrity.